NEEDS ANALYSIS ON ENGLISH TEACHING MATERIALS OF BIDIK MISI PROGRAM AT INSTITUT AGAMA ISLAM NEGERI (IAIN) BONE - Raiasah Mega Amaliyah; Muhammad Zuhri Dj.; Hasriati Nur (International Journal of Research on English Teaching and Applied Linguistics, 2022)
This research focused to find out the target and learning needs of Bidik Misi learners and know the appropriate materials to Bidik Misi Program of IAIN Bone. This research was descriptive qualitative method. The location of this research took place in IAIN Bone. Subject of the research was the fourth and sixth semester of IAIN Bone who receive Bidik Misi Scholarship. The researcher used cluster sampling technique and took 22 learners to questionnaires and 11 learners to interview. In this research, the researcher used questionnaires and interview as the instruments. The first questionnaire and interview applied to find the target needs and learning needs of Bidik Misi learners. The second questionnaire gave to the learners to know the appropriate materials. The result of this research shows that (1) the learners want to postgraduate after they have graduated and they will seldom use English in their workplace, (2) the learners’ weakness is the lack of vocabulary, (3) input in materials are texts with list of vocabulary, (4) procedures in learning process are different in each skill, (5) the learners like to study in the outside the classroom, (6) the learners want to ask and give opinion and the learners want the teacher to give them advice and correction for their task, (7) the learners need the materials which was appropriate to their study program, (8) the learners need development on all four major skills, and (9) the appropriate materials that the learners need are materials about hobbies, grammar, essay, and vocabulary.